GAD Antibodies as Key Link Between Chronic Intestinal Pseudoobstruction, Autonomic Neuropathy, and Limb Stiffness in a Nondiabetic Patient. Issue 31 (August 2015) - Maier, Andrea; Mannartz, Vera; Wasmuth, Hermann; Trautwein, Christian; Neumann, Ulf-Peter; Weis, Joachim; Grosse, Joachim; Fuest, Matthias; Hilz, Max-J.; Schulz, Joerg B.; Haubrich, Christina; Giuseppe, Scalisi.
<x xml:space="preserve">Abstract</x> Abstract Chronic intestinal pseudoobstruction (CIP) can be a severe burden and even a life-threatening disorder. Typically, several years of uncertainty are passing before diagnosis. We are reporting the case of a young woman with a decade of severe, progressive gastrointestinal dysmotility. Unusually, she had also developed an autonomic neuropathy, and a stiff limb syndrome. In addition to achalasia and CIP the young woman also developed neuropathic symptoms: orthostatic intolerance, urinary retention, a Horner syndrome, and lower limb stiffness. Careful interdisciplinary diagnostics excluded underlying infectious, rheumatoid, metabolic or tumorous diseases. The detection of GAD (glutamic acid decarboxylase) antibodies, however, seemed to link CIP, autonomic neuropathy, and limb stiffness and pointed at an autoimmune origin of our patient's complaints. This was supported by the positive effects of intravenous immunoglobulin. In response to this therapy the body weight had stabilized, orthostatic tolerance had improved, and limb stiffness was reversed. The case suggested that GAD antibodies should be considered in CIP also in nondiabetic patients. This may support earlier diagnosis and immunotherapy.